Investigating The Motivating Factors of ChatGPT Usage in Research by Postgraduate Students in Emerging Economy - Edeh, Friday Ogbu; Mundu, Muhamad Mustafa; Pandey, Rudresh; Edeh, Blessing Friday; Nabawanuka, Hamidah (Novatio : Journal of Management Technology and Innovation, 2024)
Artificial intelligence (AI) has influenced research rituals, beginning from its rigor, purposefulness, dependability, reliability, validity, and reporting. Before the advent of AI, postgraduate students were saddled with parsimonious philosophical strands and similarity thresholds. But, with the current trend of AI writing tools such as ChatGPT, most students in developing educational economies have started shifting their research posts toward writing technologies. Thus, using a cross-sectional survey design, this research aims to investigate the factors that motivate management science postgraduate students to use ChatGPT for their studies. Researchers collected data from doctoral students in management science using a questionnaire. Thus, two hundred and one (201) postgraduate students drawn from three state universities in southeastern Nigeria served as the respondents in this research. The formulated research propositions were analyzed with linear regression. The study found that postgraduate students were motivated by perceived usefulness, ease of use, and enjoyment. The result of the study revealed that perceived ease of use (PEOU), perceived usefulness (PU), and perceived enjoyment (PE) have a positive significant effect on ChatGPT usage.